GROUNDWATER INVESTIGATION IN THE PIEDMONT ZONE OF HIMALAYAN FOOTHILL REGION, INDIA, USING ELECTRICAL RESISTIVITY TECHNIQUES - Ramzi abdulgafor, Asmat; alhadithi, Mufid (Iraqi Journal of Civil Engineering, 2007)
Electrical resistivity, observations well and lithological data are used for the groundwater investigation in the piedmont zone Ratmau –Pathri Rao watershed in Haridawre Districted of Uttaranchal India, The analysis of the resistivity data in the light of known lithology indicates that two aquifer (shallow and deep) are generally present in the area The resistivity of aquifers are generally varies in wide range. This is due to the presence of different size of ranges of grains condition consisting of fine sand and gravel (pebble) in the Tarai zone which further grade to coarser material (Boulder in the Bhabhar zone)